Broad scope gold(i)-catalysed polyenyne cyclisations for the formation of up to four carbon–carbon bonds. Issue 10 (27th February 2017) - Rong, Zhouting; Echavarren, Antonio M.
Abstract : The polycyclisation of polyeneynes catalyzed by gold(i ) has been extended for the first time to the simultaneous formation of up to four carbon–carbon bonds, leading to steroid-like molecules with high stereoselectivity in a single step with low catalyst loadings. Abstract : The polycyclisation of polyenynes catalyzed by gold(i ) has been extended for the first time to the simultaneous formation of up to four carbon–carbon bonds, leading to steroid-like molecules with high stereoselectivity in a single step with low catalyst loadings. In addition to terminal alkynes, bromoalkynes can also be used as initiators of polyene cyclisations, giving rise to synthetically useful cyclic bromoalkenes.